A proposed IPC-based clustering method for exploiting expert knowledge and its application to strategic planning. (February 2014) - Chiu, Tzu-Fu
In order to exploit the professional knowledge of the patent office examiners (implied in the IPC assignment) in the clustering process, a modified method (IPC-based clustering) has been proposed and applied to strategic planning. The performance of the proposed method was evaluated by comparison with two existing methods: K-Means and TwoStep of SPSS Clementine using the DB index and Dunn index. Afterwards, the IPC-based clustering (accompanied by link analysis) was applied to a practical domain (strategic planning) using the patent data of thin-film solar cell, so as to understand the possibility of implementing it in the management areas. According to the experimental results, the technical topics have been identified, and suggested strategies for companies have been generated for assisting the decision-making of top management. Finally, in future work the proposed method will be employed to other kinds of patent data to test its performance and applied to other practical domains to examine its feasibility in different management areas.